Ultrashort Pulse Laser Technology Laser Sources and Applications - Nolte, Stefan; Schrempel, Frank; Dausinger, Friedrich; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Ultrashort laser pulses with durations in the femtosecond range up to a few picoseconds provide a unique method for precise materials processing or medical applications. Paired with the recent developments in ultrashort pulse lasers, this technology is finding its way into various application fields. The book gives a comprehensive overview of the principles and applications of ultrashort pulse lasers, especially applied to medicine and production technology. Recent advances in laser technology are discussed in detail. This covers the development of reliable and cheap low power laser sources as well as high average power ultrashort pulse lasers for large scale manufacturing. The fundamentals of laser-matter-interaction as well as processing strategies and the required system technology are discussed for these laser sources with respect to precise materials processing. Finally, different applications within medicine, measurement technology or materials processing are highlighted.
Ultrashort Pulse Laser Sources -- Materials Processing -- Medical and Technical Applications.
Keywords: Physics; Optics; Electrodynamics; Lasers; Photonics; Medical physics; Radiation; Microwaves; Optical engineering; Materials -- Surfaces; Thin films; Physics; Laser Technology, Photonics; Optics and Electrodynamics; Microwaves, RF and Optical Engineering; Surfaces and Interfaces, Thin Films; Medical and Radiation Physics; Electronic books